A novel nano-fibriform C- modified niobium pentoxide by using cellulose templates with highly visible-light photocatalytic performance. Issue 9 (15th June 2020) - Dai, Qian; Yuan, Bingnan; Guo, Minghui; Zhang, Kun; Chen, Xueqi; Song, Zihui; Nguyen, Tat Thang; Wang, Xiaojing; Lin, Shudong; Fan, Jincheng; Li, Yingchun; Liu, Hu; et al.
Abstract: To improve the photocatalytic efficiency of niobium pentoxide (Nb2 O5 ) for the degradation of organic pollutants, a novel nano-fibriform C-modified Nb2 O5 (F–C/Nb2 O5 ) photocatalyst was successfully synthesized by niobium oxalate as precursor and nanofibrillated cellulose (NFC) as template and carbon source. Vacuum induced self-assembly method was used to form the nano-fibriform morphology. Compared to ordinary C/Nb2 O5 and commercial Nb2 O5, F–C/Nb2 O5 exhibited a typical three-dimensional nanorod structure with plenty of pores. The specific surface area of F–C/Nb2 O5 was 3 times that of C/Nb2 O5 . The prepared F–C/Nb2 O5 exhibited a 3.01 eV bandgap and was able to be activated under visible light while that was unable for commercial Nb2 O5 with 3.19 eV bandgap. The F–C/Nb2 O5 showed the best photocatalytic efficiency in pH value ≤ 3. After cycling for 5 times, the photocatalytic efficiency of F–C/Nb2 O5 was still 2.4 times of the ordinary C/Nb2 O5 under visible light. Meanwhile, the self-assembly mechanism and photodegradation mechanism were proposed. This study provides a new strategy to form a special nano-fibriform C-modified niobium pentoxide with extremely high photocatalytic efficiency in aqueous solutions.